Are Higher-Education Institutions Ready for Learning Analytics? Governance, Ethics, Confidentiality and Privacy - Jang, Yeona; Katz, Rebecca; Dalkir, Kimiz (Journal of Leadership, Accountability and Ethics, 2021)
University governance on the use of student feedback was studied by looking at the availability and clarity of public policies, FAQ’s, websites, and other documents made available by a sample of Canadian higher education institutions. Educational data, including student feedback data, offers institutions new opportunities to analyze and evaluate their programs in order to improve teaching and learning. However, it is imperative that datasets be used and protected in a manner that respects student privacy and promotes trust and transparency. The research revealed a number of inconsistencies in privacy governance practices, information availability, and proactivity of Canadian higher education institutions.